25.6k views
4 votes
{(24p – 66) = 3p + 43

User Karthik
by
5.1k points

1 Answer

0 votes


\text {Hello! Let's Solve this Equation!}


\text {\underline {The First Step is to Subtract 3p}}


\text {24p-66-3p=3p+43-3p}


\text {Your New Problem Is: 21p-66=43}


\text {\underline {The Next Step Is to Add 66}}


\text {21p-66+66=43+66}


\text {Your New Problem Is: 21p=109}


\text {\underline {The Final Step is to Divide 21}}


\text {21p/21=109/21}


\text {Your Answer Would Be:}


\fbox {p=109/21}


\text {Best of Luck!}

User JBradwell
by
4.5k points